2014
DOI: 10.4028/www.scientific.net/amr.905.362
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Contributing Factors on Strength Development of Lime Stabilized Artificial Organic Soils Using Statistical Design of Experiment Approach

Abstract: Lime is widely used as chemical stabilizer in soft soil stabilization. However, lime is reported to be less effective when dealing with organic soil. It is believed that the organic matter in the soil will retard the pozzolar~ic reaction which is responsible for strength enhancement. The heterogeneity nature of the organic matter in the soil makes the study complicated and reduced the repeatability of the test results. Hence, artificial organic soil with known organic matter and content are preferred by resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
2
0
0
Order By: Relevance
“…However, the unconfined compressive strength of the K7HA3 is the highest and followed by K5HA5 and pure kaolin grade S300. The findings agreed well with the previous study [23,24] in which the moisture content and density of specimens were found not to be statistically significant with the strength of stabilized soil. Figure 4 shows the experimental results on the effect of percentages of VAE copolymer emulsion on the unconfined compressive strength (UCS) of soils.…”
Section: Effect Of Organic Acid On Unconfined Compressive Strength Ofsupporting
confidence: 92%
See 1 more Smart Citation
“…However, the unconfined compressive strength of the K7HA3 is the highest and followed by K5HA5 and pure kaolin grade S300. The findings agreed well with the previous study [23,24] in which the moisture content and density of specimens were found not to be statistically significant with the strength of stabilized soil. Figure 4 shows the experimental results on the effect of percentages of VAE copolymer emulsion on the unconfined compressive strength (UCS) of soils.…”
Section: Effect Of Organic Acid On Unconfined Compressive Strength Ofsupporting
confidence: 92%
“…On the other hand, it is found that the UCS of K7HA3 is greater than K5HA5. This statement can be supported by the result of the previous research which showed that at low organic contents the soil particles tend to aggregate, whereas at higher organic contents the soil particles tend to disperse [23]. Also, the organic particles are stiff when compressed and act as rigid particles when dry, but when they absorb water, they become soft and sponge-like.…”
Section: Effect Of Organic Acid On Unconfined Compressive Strength Ofsupporting
confidence: 57%